DISCLOSURE OF SUSTAINABILITY REPORT LEGITIMACY THEORY PERSPECTIVE - Filbert Kusuma Deharlie; Aminah (ZILLZELL MEDIA PRIMA, 2024)
This study aims to empirically ascertain how the Sustainability Report is influenced by company size, profitability, audit committee, and institutional shareholding. Sustainability Report internal and external responsibility of stakeholders to the performance of the organization in achieving sustainable development goals. This study determines the population of companies included in the List of Rating – Asia Sustainability Reporting Rating (ASRRAT) awards in 2022. Purposive sampling was used for the sampling process, resulting in 11 companies and 44 observations in total. Testing research results using multiple linear regression, classical assumption testing, descriptive statistical analysis, and hypothesis testing are all part of the data analysis approach. The findings show how the disclosure of the Sustainability Report is positively influenced by company size, profitability, audit committee, and institutional shareholding.